2008
DOI: 10.1097/aog.0b013e31818ce394
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Robotic Sacrocolpopexy Compared With Abdominal Sacrocolpopexy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(138 citation statements)
references
References 16 publications
4
128
3
3
Order By: Relevance
“…Conventional laparoscopic and robot-assisted routes result in a shorter hospital stay, faster time to recovery, and lesser postoperative pain than laparotomy, with comparable short-term efficacy (5)(6)(7)(8). The United Kingdom multicenter randomized equivalence trial found that after one year follow-up, there were no differences in anatomic or subjective pelvic floor outcomes compared to open and laparoscopic techniques; however, the blood loss, postoperative hemoglobin values, and hospital stay were better in the laparoscopic arm (9).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional laparoscopic and robot-assisted routes result in a shorter hospital stay, faster time to recovery, and lesser postoperative pain than laparotomy, with comparable short-term efficacy (5)(6)(7)(8). The United Kingdom multicenter randomized equivalence trial found that after one year follow-up, there were no differences in anatomic or subjective pelvic floor outcomes compared to open and laparoscopic techniques; however, the blood loss, postoperative hemoglobin values, and hospital stay were better in the laparoscopic arm (9).…”
Section: Introductionmentioning
confidence: 99%
“…A further study by White comparing three approaches, robotic, laparoscopic and single port revealed no difference in pain, length of stay, blood loss or operating time between the three [67], with good short-term functional outcomes. Further studies confirm the good functional results using the robot showing it to be efficacious in the management of VV P [68,69] with a low complication rate and high patient satisfaction [70]. The robotic approach may assist the surgeon in dissecting over the sacral promontory [71].…”
Section: Urogynecology: Sacrocolpopexy and Hysteropexymentioning
confidence: 64%
“…The effectiveness of the da-Vinci robot system that assists surgeons in complex procedures is now supported by level II evidence (Geller, Siddiqui, J.M.Wu, & Visco, 2008). Robotic telepresence has proven itself through deployments in dangerous or unreachable environments, with applications ranging from nuclear material handling demonstrated at the Fukushima nuclear plant disaster in 2011 to planetary exploration with the Mars Rover.…”
Section: Introductionmentioning
confidence: 88%